What the thyroid cancer patient wants to know: ThyCa survey by the American Head and Neck Society Endocrine Surgery Section. Issue 9 (12th June 2020) - Dhillon, Vaninder K.; Silver Karcioglu, Amanda; Bloom, Gary; Randolph, Gregory; Lango, Miriam
Abstract: Objective: To survey a large cohort of thyroid cancer survivors from ThyCa on information needs and expectations of their treatment to better understand the pretreatment counseling, information, and support needs of this population. Methods: Anonymous survey of thyroid cancer survivors. Results: One thousand one hundred twenty‐four patients with thyroid cancer participated in the survey. Three hundred sixty‐two (37.44%) reported not having had a full understanding of their treatment plan and 407 (46.41%) reported that their thyroid cancer treatment did not conform to expectations. Patients diagnosed at younger ages were significantly more likely to report inadequate understanding of the treatment, failure of treatment to meet expectations, and call for greater attention to psychological well‐being. Older patients were more likely to report unexpected effects on speech and swallowing. Regardless of age, patients most frequently called for greater attention to management of energy levels (endorsed by 61% of respondents), psychological well‐being (50%), and weight changes (48%). Conclusions: Improvements are needed in age‐specific communication of thyroid cancer diagnosis and treatment.